2021
DOI: 10.3389/fpubh.2021.616180
|View full text |Cite
|
Sign up to set email alerts
|

Research on Disability Grading Based on ICF Functional Framework: Empirical Evidence From Zhejiang Province, China

Abstract: Through assignment method, the total score of disability in multiple dimensions is obtained, and it is divided into five functional states—severe disability, partial disability, moderate disability, mild disability, and health—according to the score, and the probability of death is constructed. Using the Chinese Longitudinal Healthy Longevity Survey (CLHLS) database tracking survey data, by constructing a multistate transition probability matrix, the empirical calculation of the multistate disability transfer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 28 publications
(28 reference statements)
0
14
0
Order By: Relevance
“…Compared with current LTCI policy researches, such as Kim & Lim [ 14 ], Choi et al [ 18 ], Yasutake et al [ 29 ], and Ma et al [ 13 ], based on the analysis of LTCI medical cost control utility, this study puts group benefit fairness into evaluation of the implementation effect of LTCI policy for the first time, which is a great breakthrough in research perspective and research content. In respect of research methods, we use the instrumental variable method to reduce the estimation errors caused by sample selection errors, which can effectively improve reliability of research conclusions, which is consistent with the research methods of Boo et al [ 16 ] and Liu [ 5 ].…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Compared with current LTCI policy researches, such as Kim & Lim [ 14 ], Choi et al [ 18 ], Yasutake et al [ 29 ], and Ma et al [ 13 ], based on the analysis of LTCI medical cost control utility, this study puts group benefit fairness into evaluation of the implementation effect of LTCI policy for the first time, which is a great breakthrough in research perspective and research content. In respect of research methods, we use the instrumental variable method to reduce the estimation errors caused by sample selection errors, which can effectively improve reliability of research conclusions, which is consistent with the research methods of Boo et al [ 16 ] and Liu [ 5 ].…”
Section: Discussionmentioning
confidence: 57%
“…Medical security or nursing service policies are not as important as expected [ 30 , 31 ], and, compared with factors such as gene, environment, region and income, the health effect of medical security is actually quite small [ 32 , 33 ]. From the health behavior perspective, after implementation of LTCI, whether the elderly can improve their health through the utilization of LTC services has been studied [ 5 , 34 ]. Moreover, Nemoto et al [ 35 ] considered the difference in physical vulnerability of people covered by LTCI as the object and found that the physical function of vulnerable elderly people became worse than before.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of research content, this study focuses on the formation mechanism of risk of individual health shock and ADL disability of the older adults, under the influence of SES. In detail, we divided the ADL level of older adults into five levels: health, mild disability, moderate disability, partial disability and severe disability [ 22 , 23 ]. Also, the variable of SES is measured from the three dimensions of individual education level, economic status and pre retirement occupation [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research shows that short- and medium-term air pollution can significantly increase medical expenses. When air pollution is optimized, the total medical expenses can be effectively reduced ( 32 – 34 ). However, the medical costs associated with asthma and other respiratory diseases increase when the concentration of air pollutants increases, especially inhalable particulate matter ( 35 , 36 ).…”
Section: Literature Reviewmentioning
confidence: 99%